A mobile microfocal x-ray diagnostic complex in the imaging of premature newborns - Alexander V. Alkhazishvili (Eco-vector, 2021)
Background: In the modern clinical practice, providing fast, mobile and high-quality bedside X-ray imaging is important for managing newborn children . Thus, the development of new devices with all these features and their clinical application are of considerable significance. Aims: Estimation of the diagnostic capabilities of a microfocal X-ray diagnostic complex for the imaging of premature newborns. Methods: The study was performed at the facilities of Almazov National Medical Research Centre. The study included X-ray examinations of 156 premature newborns using the method of microfocus radiography: 139 X-ray images of the chest, 17 X-ray images of the abdomen. The imaging was performed using the projection magnification technique with a patient positioned close to the X-ray source. Results: The microfocal X-ray images showed the necessary quality for the diagnosis of pathological changes in the chest and abdomen in infants. The patient dose estimation was based on the radiation output of the X-ray unit and the tube current-time product. For the maximum values of the tube voltage, tube current and exposure time, the effective doses did not exceed 0.02 mSv, corresponding to the negligible radiation risk category. Conclusions: Microfocal radiography allows performing informative X-ray examinations of premature newborns, especially using the projection magnification technique. The use of a microfocal X-ray diagnostic complex allows reducing patient doses, increasing the mobility and usability of the X-ray equipment. The first experience of clinical application of microfocal radiography in neonatology and pediatrics with the projection magnification of an X-ray image was found successful. The implementation of this device in pediatric clinical practice will optimize the tactics of managing premature newborns.